Moscow experience in the work of Zaha Hadid - Lebedeva, Tatyana (project baikal, 2016)
Zaha Hadid’s works are represented in the article by the Dominion Tower Office Building – the only one project of hers realized in Moscow so far. Zaha Hadid’s early creative work was inspired by Russian avant-gardists and constructivists. The article shows the impact it had on the Moscow project.
Keywords: the architect of the future; constructivism in modern architecture; author's style